Evaluasi Implementasi Penganggaran Berbasis Kinerja di Masa Pandemi Covid-19 - Gratia Mastauly Situmorang; Dwi Martani (Politeknik Ganesha Medan, 2023)
The research aims to evaluate performance-based budgeting during the Covid-19 pandemic at the Ministry of State Secretariat. The Covid-19 pandemic has become a global issue, so government agencies have refocused the national budget. Meanwhile, performance gains can be realized if supported by an adequate budget. The research used a case study strategy with a qualitative approach, single case study method, qualitative descriptive data analysis on single unit analysis with data documentation instruments and group discussion forums (FGD). This research is interesting because it examines strategic ministries during the Covid-19 pandemic through FGD instruments. The results of data analysis for 2020-2022 show that the absorption of the Ministry of State Secretariat's budget is on average <95% due to the high and dynamic intensity of the activities of the President/Vice President, which is a particular challenge in budgeting. Significant fluctuations in output efficiency occurred due to savings in official travel costs during the pandemic. The value of output and outcome achievements is relatively constant and meets targets even though efficiency has increased due to digital transformation and new work patterns. The results of the study show that there are still HR constraints and priority scales, but cross-departmental collaboration is still implemented through ICT optimization when working from home. The research concludes that performance-based budgeting has been carried out in accordance with regulations as per the results of budget performance evaluations in the aspects of implementation, benefits, and context. However, the implementation is not optimal when there is a change in personnel, regulations, and applications, so that the improvement of HR competence and collaboration needs to be carried out continuously.